From the Editors - Sibel Sakarya Yucel Demiral (Turkish Society of Public Health Specialists, 2017)
Prof. Ray W. Guillery, English Editor of our Journal has passed away... Prof. Guillery (Greifswald-Germany; 1929) is a British physiologist and neuroanatomist. He began his education as a medical student at University College London (UCL). He obtained his BSc and his PhD in Anatomy. Guillery taught at UCL for 11 years. He helped to start the new graduate program in neuroscience in several Universities. In 1989, Guillery was the founding editor-in-chief of the European Journal of Neuroscience. He was Honorary Emeritus Research Fellow at the Anatomical Neuropharmacology Unit at Oxford since 2010. Prof R Guillery joined Turkish Journal of Public Health family with the second issue of 2008 and since then he worked with us for English edition of 24 issues voluntarily;  always in time and with a unique care. He would not only correct English grammar mistakes in manuscripts; but provide significant contribution by indicating unclear points as an interested reader; despite public health was not his area. During time, he developed interest to several public health issues and discussed with us. Ray was not only good in words but numbers; he would detect calculation mistakes in the manuscripts which were missed by reviewers and/or editors. Prof Ray Guillery conducted a course on Scientific Writing in English during National Public Health Congress which was held in Bursa. He has been always keen and generous in sharing his knowledge and experience. He never stopped his works in neuroscience and anatomy and completed his last book a few weeks before passing away. A big loss for scientific world and for our Journal. We express our appreciation for his contribution to our Journal and to all of us.  Sibel Sakarya, Yücel Demiral